Evaluation of Some Micronutrients among Sickle Cell Disease Patients in Benin City, Edo State, Nigeria. - Digban, A.K., Okogun, G.R.A., Adu, M.E.* and Jemikalajah, J.D. (Sokoto Journal of Medical Laboratory Science)
Sickle cell disease (SCD) is an inherited disorder of haemoglobin caused by a single nucleotide substitution of thymidine for adenine (GAG-GTG) of the β-chain that results in the amino acid valine instead of glutamic acid. This congenital haemoglobin mutation alters this balance and creates a pro-oxidant and micronutrient reactive milieu. This study investigated some micronutrients status of sickle cell patients. A total of one hundred (100) participants were recruited for this study which consists of fifty (50) sickle cell subjects and fifty (50) apparently healthy age -matched individuals were monitored as control. Blood samples were collected by venepuncture and some micronutrients (Iron, Zinc, Manganese, cobalt, Calcium and Magnesium) were analyzed using Atomic Absorption Spectrophotometer. All parameters were significantly decreased in sickle cell patients when compared with apparently controls (p<0.05). Considering the results obtained in this study, it could be inferred that sickle cell subjects are predisposed to nutritional deficiencies. We therefore advocate routine assessment of micronutrients in sickle cell patients. It may be necessary to routinely provide nutritional supplements for sickle cell disease patients in Nigeria.